The Influence of Project-Based Learning on Students' Critical Thinking Skills in Islamic Religious Education - Ahmad Izzul Haq; M. Yusuf Tahir; Nursalam Nursalam (Yayasan Letiges Konsultan Sosial, 2025)
This research aims to analyze the influence of project-based learning (PjBL) on critical thinking skills in Islamic Religious Education subjects at SMA Insan Cendekia Syech Yusuf Gowa. The research focuses on evaluating the effectiveness of implementing the PjBL model in enhancing the quality of learning processes oriented toward active, contextual learning, particularly in developing students' critical thinking abilities. The approach employed is quantitative with a quasi-experimental design. The research subjects consisted of two classes: an experimental class that received a project-based learning model and a control class that used conventional methods. Data were collected through observation, critical thinking skills questionnaires, and learning outcome tests. Data analysis was conducted using t-tests and MANCOVA to measure differences and assess the model's influence on the dependent variables. The research results indicated that project-based learning was implemented very well, with an average implementation rate of 3.73 on a scale of 4. The average critical thinking skills score increased from 61.90 to 82.38, while the average learning outcomes score increased from 68.81 to 87.24. Statistical analysis demonstrated a significant effect of the PjBL model on the simultaneous improvement of both variables. These findings affirm that PjBL is effectively applied in Islamic Religious Education, as it can develop critical thinking, collaborative, and reflective skills that contribute to achieving Sustainable Development Goal 4 on Quality Education.